A Meta-Model Of E-Collaboration In Classroom Organization And Cbc Learners Performance In Public Primary Schools In Kilifi County - Ratanya, Scholastica (Advances in Social Sciences Research Journal, 2024)
Classroom management is a significant aspect that matters a great deal to enhance student learning. Past studies have established a link between classroom management and student performance. Specifically, this study intends to fill existing knowledge gap on classroom organization and arrangement and classroom management time. This paper seeks to establish the effect of classroom layout of the seating patterns on students’ outcomes on improving CBC learners’ performance in primary schools in Kilifi County. The study also aims at finding out the effect of organization of classroom occurrences on improving CBC learners’ performance in primary schools in Kilifi South Sub-County. Two independent variables will guide this study and a dependent variable. This study was significant in providing support to both public and private schools during this COVID-19 era where learners are using more technologically based learning equipment and materials. This study will also provide novel insights to the Ministry of Education and policy makers in enacting suitable polices to enhance teaching and learning in primary schools. and Eison’s Active Learning Continuum and Classroom-Based Model of Student Engagement were the foundational theories of this study. Descriptive research design was applicable for this study a nd t he target population of the study was 65 public primary schools in Kilifi Sub-Counties. Sampling was carried out by use of simple random sampling and convenience sampling where a sample size of 30% of the population was achieved hence a 20 Public primary schools form Kilifi County. Structured questionnaires were used as the focal data collection instrument. Classification of data was done and data analysis was carried out by use of Statistical Package for Social Sciences (SPSS), (version 22.0). Data was presented by descriptive and inferential statistics for simplification purposes. One of the findings of this study was that most primary schools in Kilifi Sub-Counties had similarities and differences in the classroom organization and arrangements patterns for the entire of terms of the year. The implication of this phenomenon was that classrooms are arranged to enhance student’s learning. This reflects the significance of primary school teachers with appropriate materials and equipment to establish appropriate classroom arrangements to enhance learner performance. One of the findings from this study was the diversity efforts in enhancing CBC learners team learning. It was concluded that efforts used by CBC teachers to ignite creativity through sharing of opinions and experiences provided new ways of learning. The study recommends that CBC teachers should be facilitated in order to share online space organization and enhance e-collaboration with teachers from other environments. This was significant as it would aid in enhancing learner’ concentration enhancing the ability of good time management. This was projected to improve overall learner’ outcomes.